2018
DOI: 10.3390/nu10030370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Versus Moderate Glycemic Index Diets on Aerobic Capacity in Endurance Runners: Three-Week Randomized Controlled Crossover Trial

Abstract: The glycemic index (GI) of ingested carbohydrates may influence substrate oxidation during exercise and athletic performance. Therefore, the aim of this study was to assess the effect of low- and moderate-GI three-week diets on aerobic capacity and endurance performance in runners. We conducted a randomized crossover feeding study of matched diets differing only in GI (low vs. moderate) in 21 endurance-trained runners. Each participant consumed both, low- (LGI) and moderate-GI (MGI) high-carbohydrate (~60%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
4
26
0
3
Order By: Relevance
“…7 To date, the available evidence suggests that diets based on low-GI carbohydrate-rich foods improve insulin sensitivity and blood glucose control in people with prediabetes and diabetes mellitus, reduce high blood fat levels, and may help prolong peak physical performance during endurance events. [25][26][27][28][29] Because non-insulin-dependent diabetes mellitus and coronary heart disease continue to be major causes of illness and death in all industrialized countries, the extent to which the glycemic impact of diets influences both the onset and progression of these diseases is an issue of great importance. Nonetheless, the effects of BTI320 in this population have yet to be described, and further studies are ongoing to more fully elucidate any effects regarding diabetic-related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 To date, the available evidence suggests that diets based on low-GI carbohydrate-rich foods improve insulin sensitivity and blood glucose control in people with prediabetes and diabetes mellitus, reduce high blood fat levels, and may help prolong peak physical performance during endurance events. [25][26][27][28][29] Because non-insulin-dependent diabetes mellitus and coronary heart disease continue to be major causes of illness and death in all industrialized countries, the extent to which the glycemic impact of diets influences both the onset and progression of these diseases is an issue of great importance. Nonetheless, the effects of BTI320 in this population have yet to be described, and further studies are ongoing to more fully elucidate any effects regarding diabetic-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, a growing body of research has shown that the overall glycemic impact of subject diets can influence the development of insulin resistance and the risk of associated diseases such as heart disease and diabetes mellitus, independent of the total carbohydrate content of the diet . To date, the available evidence suggests that diets based on low‐GI carbohydrate‐rich foods improve insulin sensitivity and blood glucose control in people with prediabetes and diabetes mellitus, reduce high blood fat levels, and may help prolong peak physical performance during endurance events . Because non‐insulin‐dependent diabetes mellitus and coronary heart disease continue to be major causes of illness and death in all industrialized countries, the extent to which the glycemic impact of diets influences both the onset and progression of these diseases is an issue of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained information was adjusted using the album of photographs of food products and dishes elaborated by The National Food and Nutritional Institute in Warsaw. As in our previous works [ 3 , 21 , 22 ], quantitative analysis of the composition of the daily food rations was performed using the Dietetyk 2016 (Jumar, Poznań, Poland) software package. This program is based on a database elaborated by The National Food and Nutritional Institute.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, individuals presenting a favorable genotype for endurance sports according to ACE gene presented a higher mean glycemic index intake than the other genotypes. Although it seems clear that carbohydrate consumption is needed to maintain glycogen stores, whether these macronutrients are preferable to be complex or with a high glycemic index appears to be controversial, as there are studies that point out that moderate glycemic index diets improves exercise performance (Durkalec-Michalski et al, 2017) while others support the low glycemic index (Durkalec-Michalski et al, 2018). A possible explanation of this controversy may lie in the fact that the unfavorable ACE genotype for endurance performance has also been linked to lower glucose tolerance (Schuler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%